Ni-Doped TiO2 Nanotubes for Low Concentration H2 Sensing - Abbasi, S. (Springer Science and Business Media B.V., 2021)
The Growing importance of H2 in different fields such as in industries, fuel cell technology and medicine has increased the need for rapid detection of H2. In this work, H2-gas sensitive n-type material based on undoped and Ni-doped TiO2 nanotubes were synthesized and their H2 sensing properties were investigated. For the first time, Ni was doped into anodic nanotubular TiO2 by hydrothermal reaction. Morphological and crystallographic analysis by electron microscope and X-ray diffraction suggested that Ni doping has no effect on surface morphology of the tube structure. Whereas, X-ray photoemission spectroscopy revealed that Ni has been incorporated interstitially in the TiO2 network, which in turn induced effective reduction of bandgap, thereby improving the gas sensing properties towards low concentration of H2 gas. The H2 sensing properties of the nanotubes exposed to 20, 70 and 100Â ppm of H2 were investigated at operating temperature of 50, 100 and 200Â Â°C. Ni-doped TiO2 nanotube effectively improved the hydrogen sensing of the sensor compared to undoped TiO2 sensor. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.